Enhanced Bio-Electro-Fenton degradation of phenolic compounds based on a novel Fe–Mn/Graphite felt composite cathode. (November 2019) - Li, Biao; Yan, Zhi-Ying; Liu, Xiao-Na; Tang, Chen; Zhou, Jun; Wu, Xia-Yuan; Wei, Ping; Jia, Hong-Hua; Yong, Xiao-Yu
Abstract: Phenolic compounds are problematic byproducts generated from lignocellulose pretreatment. In this study, the feasibility degradation of syringic acid (SA), vanillic acid (VA), and 4-hydroxybenzoic acid (HBA) by Bio-Electro-Fenton (BEF) system with a novel Fe–Mn/graphite felt (Fe–Mn/GF) composite cathode were investigated. The nano-scale Fe–Mn multivalent composite catalyst with core shell structure distributed more evenly on GF surface to form a catalyst layer with higher oxygen reduction reaction performance. Accordingly, the maximum power density generated with Fe–Mn/GF cathode was 48.1% and 238.9% higher than Fe/GF and GF respectively, which further enhanced the in situ generation of H2 O2 due to the superiority of nano-scale core shell structure and synergistic effect of Fe and Mn species. The degradation efficiency of the three phenolic compounds in the BEF system could reached 100% after optimization of influencing parameters. Furthermore, a possible SA degradation pathway by BEF process in the present system was proposed based on the detected intermediates. These results demonstrated an efficient approach for the degradation of phenolic compounds derived from lignocellulose hydrolysates. Highlights: A novel Fe-Mn/graphite felt composite cathode was simply developed by a one-step approach. Core shell Fe-Mn multivalent catalyst evenly distributed on the surface of GF cathode to enhance OH generation. Complete removal of phenolic compounds was achieved due to the excellent catalytic activity of composite cathode. The possible degradation pathway of syringic acid by Bio-Electro-Fenton process was proposed.